Keikutsertaan Masyarakat dalam Membangun Kualitas Pelayanan Publik - Endang Wirjatmi Trilestari (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
As we all know, service is an interactive process between the server and its client. Both contain the values and hopes in line with their norms and perception. They are the basic expectation put down by the server and client to decide the service quality. The conceptual transposition of total quality management (TQM) in private service to the public service will bring about the influence to the organizational activities. This is the action carried out by the government to legalize their conduct. Therefore, the service quality in public service may not merely be resolved by the government as the service provider but also by the society, either as common people, the needs, consumers, or citizen.